Religious Influences on the Poetry of Maulana Zafar Ali Khan - Iqbal, Saima; Akhtar, Parveen; Ahmad, Shumila Mushtaq (sourcecoder, 2023)
Maulana Zafar Ali Khan was born on January 19, 1873 in Kot Meerut city of Wazirabad. He was also a poet, an editor and an active political the era of poetry is from the First World War to the sixties. Even after the partition, your poems published in the period are very strong with regard to religious tendencies. Maulana’s unique identity in “Hymd” writing has been established till date. They started a new morning with new words of praise and fresh thoughts. Maulana Zafar Ali Khan’s poetic efforts have been published in the form of “Baharistan” “Nigaristan” and “Chamistan". Maulana Zafar Ali Khan’s poetry has three aspects. One side is political, the other is about feelings and emotions, and the third is the religious side of poetry. Some of his poems are filled with praise and worship of the Lord of the worlds, while some are an understanding of the phenomena of nature. Start of His “Kuliat” with the name of religion of Islam and praise of Allah. This article presented religious influences on the poetry of Maulana Zafar Ali Khan.